Pengaruh Diferensiasi, Prestise, dan Performa Sistem Operasi terhadap Keputusan Pembelian Handphone Iphone di Kabupaten Magelang - Dewi, Icha Septiani; Prasojo, Eko (CV. Kurnia Grup, 2024)
This study aims to determine the influence of differentiation, prestige, and operating system performance on the purchasing decisions of iPhone smartphones in Magelang Regency. This quantitative research was conducted from May 14, 2024, to June 7, 2024. The study population includes all consumers using iPhone products in Magelang Regency, with a sample of 160 respondents. The sampling technique used was non-probability sampling with a purposive sampling approach, and data were collected through questionnaires. Data analysis was performed using multiple linear regression analysis techniques. The results of the analysis show that differentiation has a positive and significant effect on the purchasing decision of iPhone smartphones in Magelang Regency, with a t-value of 3.813. Prestige also has a positive and significant effect on purchasing decisions, with a t-value of 3.869. The performance of the operating system has a positive and significant effect on purchasing decisions, with a t-value of 10.414. Simultaneously, differentiation, prestige, and operating system performance have a positive effect on the purchasing decision of iPhone smartphones in Magelang Regency, with an f-value of 325.851, which is greater than the f-table value of 2.662. These findings highlight the importance of these three factors in influencing consumer preferences for iPhones in Magelang Regency.